The Legal Consequences Of The Unregistered Notarial Agreement Related To Paragraph 40 Government Regulation No. 24 Of 1997 About Registration Of Land On The Perspective Of Legal Philosophy - Vediyas Puspa Yunansa; Umar Ma'ruf (Jurnal Akta, 2018)
The land disputes caused by unregistered notarial agreement according to Paragraph 40 Government Regulation No. 24 the Of 1997 about registration of the land creates a legal issue in the society. The unfinished process of implementation causes legal uncertainty to all parties. The authentic agreement or certificate of ownership has the similar legal force and valid to all the holders. The legal consequences of the unregistered notarial agreement related to Paragraph 40 Government Regulation No. 24 the Of 1997 about the Land Registration will cause “null and void”. So the legal position related to the ownership of the land title certificate is undamaged (the legal issue doesn’t change) according to the rights holder written on it. There are two ways of completion, which are the land dispute resolution by Court (Litigation) and the land dispute resolution by non-Court (Non-Litigation).Keywords: Notarial Agreement; Land Registration; Legal Philosophy.